Implementasi Profil Pelajar Pancasila Berbasis Budaya Literasi dalam Mata Pelajaran Pendidikan Pancasila di SMA Negeri 5 Semarang - Asyhar, Rifky Latieful; Haryati, Titik; Wahyuni, Endang Sri; Sudrajat, Rahmat (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Implementation of the Pancasila Student Profile based on literacy culture in Pancasila Education subjects at SMA Negeri 5 Semarang. This research was motivated by the lack of interest and awareness of students in promoting literacy culture, but something different was shown by SMA Negeri 5 Semarang by making various efforts to foster literacy culture through the Pancasila Student Profile. The aim of this research is to obtain data regarding the implementation of the Pancasila Student Profile based on literacy culture in Pancasila Education subjects at SMA Negeri 5 Semarang. The method used in this research is qualitative research using a descriptive approach. After carrying out research with various respondents, the researcher then processes the data and conclusions can be drawn in the form of data analysis results. The research results show that the implementation of the Pancasila Student Profile based on literacy culture in Pancasila Education subjects has been carried out well. This is realized in various kinds of activities that support literacy activities and are adapted to the six dimensions in the Pancasila Student Profile. The problems obtained are lack of student attention, lack of communication and collaboration. The solution that can be taken to overcome these problems is to increase communication and collaboration, involve related parties, and carry out monitoring and evaluation activities.